Reliability analysis and risk-based methods for planning of operation & maintenance of offshore wind turbines - Sørensen, John Dalsgaard (Volume 9: Offshore Geotechnics; Torgeir Moan Honoring Symposium, 2017)
Reliability analysis and probabilistic models for wind turbines are considered with special focus on structural components and application for reliability-based calibration of partial safety factors. The main design load cases to be considered in design of wind turbine components are presented including the effects of the control system and possible faults due to failure of electrical / mechanical components. Considerations are presented on the target reliability level for wind turbine structural components. Application is shown for reliability-based calibrations of partial safety factors for extreme and fatigue limit states are presented. Operation & Maintenance planning often follows corrective and preventive strategies based on information from condition monitoring and structural health monitoring systems. A reliability- and risk-based approach is presented where a life-cycle approach is used. An example with wind turbine blades is considered using the NORCOWE reference wind farm. Copyright © 2017 by ASME